Student Life in Canadian Universities: The Lessons of History - Axelrod, Paul (Canadian Journal of Higher Education, 1990)
This article explores the relationship between the history of the student experience and contemporary student life. It identifies enduring patterns in three areas: the social origins of students, student culture and activism, and the perceived academic quality of students. Reflecting their predominantly middle class backgrounds, university students have craved social status and feared the prospect of downward mobility, particularly in hard economic times. They have forged a student culture which serves to relieve academic tensions and strengthen their claim to social distinctiveness. Sexist outbursts by male students, past and present, speak to fundamental feelings of insecurity in the face of feminist movements. Political activism among a sizable minority of students, which predated the 1960s, now shows signs of re-emergence at a time when students sense that their long term goals may be frustrated. Finally, the professorial contention that students are academically less competent than ever has been heard before. A historical perspective, brought to this and other issues, should deepen understanding of the nature of student life.